2021
DOI: 10.1002/mgg3.1652
|View full text |Cite
|
Sign up to set email alerts
|

First reported case of Doyne honeycomb retinal dystrophy (Malattia Leventinese/autosomal dominant drusen) in Scandinavia

Abstract: Background Doyne honeycomb retinal dystrophy (DHRD)/malattia leventinese (ML) is an autosomal dominant, progressive retinal disorder characterized by massive central retinal drusen often partly coalescent forming a characteristic honeycomb‐like pattern. Debut of vision loss often occurs in early to mid‐adulthood, and the degree varies. A single variant in EFEMP1: c.1033C>T (R345W) has been identified as the cause in all cases. Methods Following DNA isolation, exome sequencing was performed in seven genes assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Black circles plot proportions from the UK (present study), from an early large study of five families, 14 and from many cases pooled from many subsequent reports. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] The red diamond plots the proportion when all these cases are pooled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Black circles plot proportions from the UK (present study), from an early large study of five families, 14 and from many cases pooled from many subsequent reports. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] The red diamond plots the proportion when all these cases are pooled.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier paper 14 that pointed to the relevant chromosomal locus did show pedigrees for five families (92 affected individuals), from which numbers of affected males and females could be extracted (these were 40 and 52, respectively). Since then, several publications have reported additional cases [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] : these cases were reviewed (avoiding mutual overlap or overlap with the cohort in the current study); of 55 reported patients, 20 were males and 35 were females. The bottom of Figure 2 plots proportions with CIs.…”
Section: Pooling With Previously Published Best and Efemp1-associated...mentioning
confidence: 99%
“…DHRD is associated with a missense mutation, Arg345Trp (R345W), in the EFEMP1 (epidermal growth factor containing fibrillin-like extracellular matrix protein 1) gene that leads to the accumulation of drusen in the macula between the RPE and Bruch’s membrane from a young age [ 79 , 80 , 81 ]. As the disease progresses, choroidal neovascularization and large geographic atrophy can result in an acute reduction in visual acuity, metamorphopsia, or paracentral scotoma, which usually occur in the fourth–sixth decades of life [ 82 , 83 ]. Clinically, DHRD is characterized by the drusen found around the optic nerve head, as well as the drusen that forms radial streaks from the center of the macula [ 80 , 82 ].…”
Section: Application Of Electrophysiology In Macular Dystrophiesmentioning
confidence: 99%
“…EFEMP1 encodes the epidermal growth factor containing fibrillin like extracellular matrix protein [2] . It is characterized by the accumulation of macular and peripapillary yellow white deposits (drusen) between retinal pigment epithelium and bruchs membrane [3] . Visual acuity is preserved until central atrophy; pigment proliferation or choroidal neovascularization develops [4,5] .…”
Section: Introductionmentioning
confidence: 99%